The Environmental Consequences of Altered Nitrogen Cycling Resulting from Industrial Activity, Agricultural Production, and Population Growth in China - G.X. Xing; Z.L. Zhu (The Scientific World Journal)
Human activities exerted very little effect on nitrogen (N) cycling in China before 1949. Between 1949 and 1999, however, rapid economic development and population growth led to dramatic changes in anthropogenic reactive N, inputted recycling N, N flux on land, N2O emission, and NH3 volatilization. Consequently, these changes have had a tremendous impact on the environment in China. In the current study, we estimated the amount of atmospheric wet N deposition and N transportation into water bodies from the watersheds and major valleys in China. Additionally, we addressed issues on leaching and accumulation of NO3 in the farmland under different climate zones, land use, and cropping systems as well as the potential influence of NO3 on underground water in China.